Digital Marketing for Young Entrepreneurs: Counselling at Global Cahaya Nubuwwah Insani School, Purwakarta - Ayu Ekasari; Yosephina Endang Purba; Cicilia Sriliasta Bangun; Havidz Kus Hidayatullah; Acep Riana Jayaprawira (Edumedia Solution, 2026)
The rapid development of the digital economy creates new opportunities for young people to participate as entrepreneurs. High school students, despite being active with digital technology and social media, are unaware of their benefits. Yet, it is important for entrepreneurs to optimize digital technology when marketing their products. The Community Service Team from the Faculty of Economics and Business Universitas Trisakti held a digital marketing counselling program for high school students studying at Global Cahaya Nubuwwah Insani (GCNI) in Purwakarta. The problem faced by the GCNI school was the low understanding of students about digital marketing which is very important for them studying to become young entrepreneurs. The program was aimed to enhance students’ understanding of digital marketing, its implementation and strategies for measuring its performance. The counselling method consisted of discussion and sharing experiences in using digital technology. To evaluate the effectiveness of the program, students were given two similar questionnaires before and after the program was conducted. The result of the descriptive analysis of the pre and after questionnaires indicate that students’ understanding of digital marketing concept improved after they joined the counselling program. The findings suggest that counselling is an effective educational approach to increasing students’ knowledge about digital marketing and strengthening their entrepreneurial spirit.